Tullock challenges: Happiness, revolutions and democracy - Bruno S. Frey (Center for Economic Studies and ifo Institute (CESifo), 2011)
Gordon Tullock has been one of the most important founders and contributors to Public Choice. Two innovations are typical 'Tullock Challenges'. The first relates to method: the measurement of subjective well-being, or happiness. The second relates to digital social networks such as Facebook, Twitter, or to some extent Google. Both innovations lead to strong incentives by the governments to manipulate the policy consequences. In general 'What is important, will be manipulated by the government'. To restrain government manipulation one has to turn to Constitutional Economics and increase the possibilities for direct popular participation and federalism, or introduce random mechanisms.
Keywords: D72; H10; I31; P16; D02; 330; happiness; social networks; constitutional economics; random mechanisms; public choice; Zufriedenheit; Disparitätsmaß; Online-Netzwerk; Informationspolitik; Manipulation; Verfassungsökonomik; Demokratie